Benefícios e aceitação dos escritórios de gerenciamento de projetos na administração pública - Bittencourt, Felipe Fernandes de Moraes (2014)
Projects are currently indispensable part of organizations. The field of project management is gaining importance and organizations seek ways to ensure that your projects are more effective and efficient increasing their profit. Within this context, the project management office emerges as one way of leveraging project management within organizations. In public administration, offices are still seen as a way to make the transition from an management model oriented processes to another results oriented model. The literature highlights its many qualities, but studies show that people still do not have clarity of the value generated by the offices. This study found what are the perceived benefits of project management offices in public administration and also their acceptance within the organization. The research was conducted through a multiple case study where interviews were addressed through a structural content analysis that resulted in a structure that relates the benefits of project management offices and their acceptance. The structure shows how organizational factors lead to resistance and low acceptance to the project office and its functions, while the functions generate benefits that are responsible for legitimizing the offices and increase their acceptance. The scenario placed is criticai to understand the time required for the office can add value to the organization.